ANALISIS PERBANDINGAN ANTARA HARGA APPRAISAL DAN HARGA ZONA NILAI TANAH UNTUK GANTI RUGI JALAN TOL MANADO - BITUNG (Comparison Analysis Between Appraisal Prices and Land Value Zone Price for Compesation of Manado-Bitung Toll Road) - Windarto nFN; Grace A. J. Rumagit; Leonardus Ricky Rengkung (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
This study aims to compare the appraisal price with the land value zone (ZNT) price for compensation for the Manado-Bitung toll road.Â  The study was carried out for eight months, starting from February 2021 to October 2021. This type of research was quantitative descriptive to determine the price disparity with land value zones. The types of data collected consisted of primary data and secondary data.The results showed a very significant difference between the amount of compensation based on the appraisal price compared to the ZNT price on land acquisition for toll roads in Bitung City. The total compensation based on the appraisal price was IDR 21,976,158,461, while the total compensation based on ZNT was IDR. 35,792.424,000 or 1:1.36. The percentage change in the compensation price based on the appraisal price and the value of the Land Value Zone Map was -38.60%.